A Critical Evaluation on Akala Palitam - Anupriya P.S; Arun Pratap; Lekshmi R; Arjun Chand C P (International Journal of Ayurveda and Pharma Research, 2022)
Hair color reflects the health of an individual and the discolored hair indicates the pathological state. Palitam is a physiological process when it occurring in old age. Whereas Akala Palitam (premature graying) is a pathological condition manifests in early stages of life. It is characterized byVivarna Kesha (discolored hair) along with altered hair texture and the predominant Dosha attributes Vivarnata to Kesha. Hair color is determined by a pigment called melanin (relative proportions of eumelanins and phaeomelanins) in hair follicles. Diffuse loss of hair melanin during early stages of liferesults in premature graying. In Ayurveda, Bhrajaka Pitta, one among the five types of Pitta located in skin is responsible for the attribution of hair colour. Thus it performs the function similar to melanin pigment in hair follicles. When there is Pitta dosha Vridhi in Rasadhatu along with vitiation of other two Doshas it leads to manifestation of Vivarna Kesha with altered hair texture thus results in Akala Palitam. It is a type of Raspradoshajavikara in which the signs and symptoms varies based on the predominant Dosha. Treatment option for Akala Palitam is also specific based on predominant Dosha. So a critical evaluation on Akala Palitam is essential to understand the etio-pathogenesis of the disease for its better management.